2014
DOI: 10.4103/0971-7749.131868
|View full text |Cite
|
Sign up to set email alerts
|

Postaural incision closure in single layer versus multiple layers: A comparison

Abstract: IntroductIonBy tradition, the postaural incision is closed in two or three layers. The layers consisting of periosteum, soft-tissue, and skin, each layer being closed separately. It not only consumes more of suture material, but also plenty of surgeon's time, sometimes the time for suturing equals or exceeds the time taken for mastoidectomy or tympanoplasty. The postaural incision closure can also be done in a single layer. Here, only the soft tissues and skin are sutured in a single layer. It saves both time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This is in contrast to the outcome of Moras et al, who found postoperative morbidity of 4% accounted for by wound infection and dehiscence in their cases. 15 Review of literature did not reveal any study mentioning all post-operative morbidities of either approach, only mentioning some significant complications though we feel from the patients' point of view, any morbidity is significant because it affects their ability to go for work as well as quality of life which is a major issue in all studies on surgical or other treatment modalities in the present era. Investigating cutaneous sensory deficit, Kang et al found that the sensation of the pinna returned to baseline within 3 months for sulcus incisions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is in contrast to the outcome of Moras et al, who found postoperative morbidity of 4% accounted for by wound infection and dehiscence in their cases. 15 Review of literature did not reveal any study mentioning all post-operative morbidities of either approach, only mentioning some significant complications though we feel from the patients' point of view, any morbidity is significant because it affects their ability to go for work as well as quality of life which is a major issue in all studies on surgical or other treatment modalities in the present era. Investigating cutaneous sensory deficit, Kang et al found that the sensation of the pinna returned to baseline within 3 months for sulcus incisions.…”
Section: Discussionmentioning
confidence: 90%
“…This compared well with the results of Moras et al, in their study on postaural incision closure. 15 In comparison, the transcanal group had a 2-2.5 cm incision above the root of pinna within the hairline with the graft accessed easily and closure with 3-4 sutures in a single layer which took a maximum of 10 minutes. The materials used for both approaches have also been noted, with transcanal approach requiring only half a 3.0 monocryl while postaural approach required 1 vicryl 3.0 and 1 monocryl 3.0.…”
Section: Discussionmentioning
confidence: 99%
“…The average time taken in double-layer closure was more than the singlelayer closure (3.7 minutes vs. 4.7 minutes). However, the time was saved in single-layer wound closure [18,19].…”
Section: Discussionmentioning
confidence: 99%